-6(-7x-8)+6(x-8)=-8x+7x

Simple and best practice solution for -6(-7x-8)+6(x-8)=-8x+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-7x-8)+6(x-8)=-8x+7x equation:


Simplifying
-6(-7x + -8) + 6(x + -8) = -8x + 7x

Reorder the terms:
-6(-8 + -7x) + 6(x + -8) = -8x + 7x
(-8 * -6 + -7x * -6) + 6(x + -8) = -8x + 7x
(48 + 42x) + 6(x + -8) = -8x + 7x

Reorder the terms:
48 + 42x + 6(-8 + x) = -8x + 7x
48 + 42x + (-8 * 6 + x * 6) = -8x + 7x
48 + 42x + (-48 + 6x) = -8x + 7x

Reorder the terms:
48 + -48 + 42x + 6x = -8x + 7x

Combine like terms: 48 + -48 = 0
0 + 42x + 6x = -8x + 7x
42x + 6x = -8x + 7x

Combine like terms: 42x + 6x = 48x
48x = -8x + 7x

Combine like terms: -8x + 7x = -1x
48x = -1x

Solving
48x = -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
48x + x = -1x + x

Combine like terms: 48x + x = 49x
49x = -1x + x

Combine like terms: -1x + x = 0
49x = 0

Divide each side by '49'.
x = 0

Simplifying
x = 0

See similar equations:

| 5+2n=-(-3-2n) | | 3x^2+6=4 | | 5m+38=7(-2m+2)-3m | | 2m^2-4m=48 | | -2(1+6n)=-2-8n | | 37x36/6 | | x+4-6=4-x | | 3a^2+22a=-7 | | 5x+3y-13=0 | | 2=-16t^2+40t+3 | | (12x+8y)-(4x-2y)= | | (5x-1)/3-(2x-3)/5=1 | | 6+9=7x-5 | | 6x+9=7x-9 | | 6-4x=3x+3 | | 6y+15=7y-28 | | 6y-14= | | 9x-12=10x+20 | | 5m+50= | | 2x-8=7y | | 7x-5=3x+12 | | 35-7c=27-3c | | f(-1)=2(-1)-3 | | (4x+45)+5x=360 | | 0.3(7x+28)=2.1(x+4) | | 2x-28=22 | | -2b-3a=-7 | | x(2y-3)dx+(x^2+1)dy=0 | | a=6b-11 | | b=45.6+0.10t | | 0.24*x=144 | | 10x-35=12x+15 |

Equations solver categories